2006
DOI: 10.1007/s00401-006-0160-y
|View full text |Cite
|
Sign up to set email alerts
|

Degeneration of cardiac sympathetic nerve can occur in multiple system atrophy

Abstract: Decreased cardiac uptake of meta-iodobenzylguanidine (MIBG) on [(123)I] MIBG myocardial scintigraphy, a sensitive biological marker for Parkinson's disease (PD), is related to cardiac sympathetic denervation in patients with PD. A slight decrease in cardiac uptake of MIBG has also been reported in some patients with multiple system atrophy (MSA). However, the pathophysiological mechanism accounting for the slight decrease in MIBG uptake in MSA remains to be elucidated. For confirmation, we examined cardiac tis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
51
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 115 publications
(53 citation statements)
references
References 18 publications
1
51
1
Order By: Relevance
“…Therefore, in LBD, as a consequence of the degeneration of the cardiac muscle sympathetic nerve, assessment of the distribution of this nerve on early images was considered useful. [10][11][12] Orimo et al 13 suggested that a decrease in myocardial 123 I-MIBG uptake in the early stage of LBD, a neurodegenerative disease, reflects the degeneration of the cardiac muscle sympathetic nerve.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, in LBD, as a consequence of the degeneration of the cardiac muscle sympathetic nerve, assessment of the distribution of this nerve on early images was considered useful. [10][11][12] Orimo et al 13 suggested that a decrease in myocardial 123 I-MIBG uptake in the early stage of LBD, a neurodegenerative disease, reflects the degeneration of the cardiac muscle sympathetic nerve.…”
Section: Discussionmentioning
confidence: 99%
“…Post-mortem histopathologic analyses have confirmed profound loss of tyrosine hydroxylase immunoreactivity in cardiac nerves [18][19][20]. In contrast, most (but not all) patients with MSA have normal cardiac sympathetic innervation [21].…”
Section: Abstract or Phrasesmentioning
confidence: 93%
“…This utility is being corroborated further by pathological observations that degeneration of the cardiac sympathetic nerve is closely related to the presence of Lewy bodies [13], progressive decrease in the heart/mediastinum ratio in Parkinson’s disease [14] and contrasting preservation of MIBG uptake and cardiac sympathetic fibers in multiple-system atrophy [15]. Because Lewy bodies and depletion of cardiac sympathetic nerve were both absent in case 2, MIBG cardiac scintigraphy, if performed, might have revealed normal uptake to indicate the absence of Lewy bodies.…”
Section: Discussionmentioning
confidence: 81%